The association between men's family planning networks and contraceptive use among their female partners: an egocentric network study in Madagascar - Alison B. Comfort; Cynthia C. Harper; Alexander C. Tsai; Jessica M. Perkins; James Moody; Justin Ranjalahy Rasolofomana; Cora Alperin; Margaret Schultz; Anja Noeliarivelo Ranjalahy; Ravo Heriniaina; Paul J. Krezanoski (BMC, 2021)
Abstract Background Ensuring women have information, support and access to family planning (FP) services will allow women to exercise their reproductive autonomy and reduce maternal mortality, which remains high in countries such as Madagascar. Research shows that women's social networks - their ties with partners, family members, friends, and providers - affect their contraceptive use. Few studies have considered the role of men's social networks on women's contraceptive use. Insofar as women's contraceptive use may be influenced by their male partners, women's contraceptive use may also be affected by their partner's social networks. Men may differ by the types of ties they rely on for information and advice about FP. It is unknown whether differences in the composition of men's FP networks matter for couples' contraceptive use. This study assessed the association between men's FP networks and couples' contraceptive use. Methods This egocentric network study was conducted among married/partnered men (n = 178) in rural Madagascar. Study participants listed who they relied on for FP information and advice, including health providers and social ties. They provided ties' gender, age, relationship, and perceived support of contraceptive use. The primary outcome was couples' contraceptive use, and explanatory variables included FP networks and their composition (no FP network, social-only network, provider-only network, and mixed network of social and provider ties). Analyses used generalized linear models specifying a Poisson distribution, with covariate adjustment and cluster robust standard errors. Results Men who had FP networks were 1.9 times more likely to use modern contraception as a couple compared to men with no FP network (95% confidence interval [CI] 1.64-2.52; p ≤ 0.001). Compared to men with no FP network, men were more likely to use modern contraception if they had a social-only network, relative risk (RR) = 2.10 (95% CI, 1.65-2.68; p ≤ 0.001); a provider-only network, RR = 1.80 (95% CI, 1.54-2.11; p ≤ 0.001); or a mixed network, RR = 2.35 (95% CI, 1.97-2.80; p ≤ 0.001). Conclusions Whether men have a FP network, be it provider or social ties, distinguishes if couples are using contraception. Interventions should focus on reaching men not only through providers but also through their social ties to foster communication and support for contraceptive use.